1993
DOI: 10.3109/00365529309098304
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Origin and Shedding of an Early Colonic Tumor Marker Defined by Adnab-9 Monoclonal Antibody

Abstract: Recent attention has been drawn to the diagnostic potential of tests based on shed colonic tumor markers. Adnab-9 monoclonal antibody raised against neoplastic, potentially premalignant colonic adenomas recognizes a marker in colonic effluent or tissue which correlates with the presence of tumors or risk of colorectal cancer. The origin of this antigen and optimal collection of colonic effluent were investigated by enzyme-linked immunosorbent assay and Western blotting. Mean Adnab-9 binding in effluent samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…We used an enriched PCR method to detect K-ras mutations as previously described [24]. ELISA was performed with Adnab-9, anti-Her-2/neu, and monoclonal antibody D4 (anti Reg I) as previously described [6]. All ELISA quantifications used optical density of the extract plated out at 5 lg protein/well after Dig Dis Sci subtracting the background.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used an enriched PCR method to detect K-ras mutations as previously described [24]. ELISA was performed with Adnab-9, anti-Her-2/neu, and monoclonal antibody D4 (anti Reg I) as previously described [6]. All ELISA quantifications used optical density of the extract plated out at 5 lg protein/well after Dig Dis Sci subtracting the background.…”
Section: Methodsmentioning
confidence: 99%
“…The Adnab-9 monoclonal antibody has shown promise as a diagnostic and premalignant marker for colorectal [6,7], gastric [8] and small intestine adenocarcinoma [9]. In those studies, neoplastic Paneth cells are often identified.…”
Section: Introductionmentioning
confidence: 99%
“…The antibody displays differential binding to adenomas and appears to recognize a subset of cells deep within the substance of the adenoma (78). Subsequently, some of these cells have been identified as Paneth-like cells (figure 1) in tissues with or at risk for CRC (79). Paneth cells in APC patients have been shown to secrete epidermal growth factor (80), a ligand for a receptor that, once activated, is mediated by tyrosine kinase.…”
Section: Monoclonal Antibodies Raised Against Colonic Polypsmentioning
confidence: 99%
“…Differences in each category were analyzed by the comparison of proportions using Fisher's exact test and least squares test for linear correlation between variables, as described previously (15)(16)(17)(18). Significance was defined as P < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Adnab-9 binding has been shown to identify a subpopulation of cells in colonic adenomatous and normal mucosa from colons bearing CRC, but not carcinomatous tissue, some of which resemble Paneth cells (PC) (13)(14)(15)(16). The presence of Adnab-9 staining in nonneoplastic colonic epithelium has been shown to be associated with an increased risk for development of colorectal cancer (13)(14)(15)(16)(17). In addition, Adnab-9 staining has a positive correlation with multiplicity and recurrence of colonic polyps and may be a predictor of future development of dysplastic polyps with recognized malignant potential in these patients (18).…”
mentioning
confidence: 99%